An expert's guide to international protocol : best practices in diplomatic and corporate relations - Monod de Froideville, Gilbert; Verheul, Mark (Amsterdam University Press, 2016)
Although modern life grows increasingly casual, in many sectors, protocol still reigns supreme. An Expert's Guide to International Protocol offers an overview of its associated practices, including those found within the context of diplomatic relations and the business world. Focusing on a wide range of countries and cultures, the book covers topics like seating arrangements, the history and use of flags, ceremonies, invitations and dress codes, and gifts and decorations. Throughout, influential diplomatic, business, cultural, and sports figures share their own experiences with protocols around the world.